2014
DOI: 10.1183/09031936.00117714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole body hypothermia on inflammation and surfactant function in asphyxiated neonates

Abstract: Hypothermia has become an evidence-based treatment for neonates with hypoxic-ischaemic encephalopathy (HIE) [1]. The usefulness of hypothermia is due to several mechanisms and among these the reduction in inflammation seems to play a relevant role [2,3]. When applied as whole body hypothermia (WBH), cooling may affect other organs as well. Recent data showed better respiratory outcomes and trends towards lower inflammation in WBH-treated preterm lambs [4], suggesting its possible usefulness to reduce lung inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…SAT was developed by Ravasio et al [28] in 2008. However, changes in this protocol were proposed later to improve the assay sensitivity (lower volume and higher molar dye/surfactant ratio) and to test the human samples of different origin,29 30 converting SAT in a useful tool to design a bedside point of care method.…”
Section: Testing Ps Activitymentioning
confidence: 99%
“…SAT was developed by Ravasio et al [28] in 2008. However, changes in this protocol were proposed later to improve the assay sensitivity (lower volume and higher molar dye/surfactant ratio) and to test the human samples of different origin,29 30 converting SAT in a useful tool to design a bedside point of care method.…”
Section: Testing Ps Activitymentioning
confidence: 99%
“…Therefore, standard solutions (STDs) were prepared by serial dilutions of the above mentioned calibrator with physiological solution (0.9% NaCl). Concentration of STDs was chosen on the basis of the concentration range previously measured in BAL samples from both neonates and infants, [6][7][8] that is, from STD 6 to STD 1: 2.00 mg/dL, 1.20 mg/dL, 0.60 mg/dL, 0.30 mg/dL, 0.15 mg/dL, and 0.00 mg/ dL as blank. QC were prepared similarly to STDs to achieve a final concentration of 1.8 mg/dL for QC high and 0.15 mg/dL for QC low.…”
Section: Calibration Curve and Quality Controls (Qc) For Urea Assaymentioning
confidence: 99%
“…1 We and other authors have published some papers using urea nitrogen measurement in BALF and using the serumto-BALF urea ratio to correct the BAL dilution in neonates and infants. [4][5][6][7][8] A measurement of urea concentrations in BALF and serum was performed in duplicate by means of a colorimetric assay (urea nitrogen suitable on Olympus AU2700). 4 Although Capoluongo et al previously reported this method as a modified protocol on Olympus instrumentation, 4 no details were provided about the setup of a standardized method to assay urea in BALF.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, it could be hypothyzed that the adrenergic stimuli may induce surfactant mobilization and production from type 2 pneumocytes. De Luca et al ., studied pulmonary surfactant activity by fluorescence analysis of adsorption and found a significant increase in surfactant function after 48 h of WBH in neonates with HIE and no injured lungs, suggesting that adaptive mechanisms could act in surfactant modulation [ 10 ]. More information and studies designed to measure surfactant composition and production during systemic hypothermia may help understanding the effect of this treatment in severe lung injury [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…De Luca et al . have recently reported significant reductions in IL-6 and IL-8 levels in Epithelial Lining Fluid during WBH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%